KOMBINASI HERBA SELEDRI (Apium graveolens, L) DAN DAUN LIDAH BUAYA (Aloe vera, L) SEBAGAI MINUMAN HERBAL INSTAN - Cahyanto, Heru Agus (Jurnal Riset Industri Hasil Hutan, 2014)
The purpose of this study was to determine the quality of herbal raw materials and consumer acceptability to  the instan tea. Celery and  aloe vera leaf have an ability to lower blood pressure. The combination of these two herbs are expected to have a synergistic effect in  this instant tea. The formulation tea showed the appropriate with the  requirements and no difference in taste, color and odor in statistic of the three formulations.Keywords:  formulation, celery, aloe vera